Resultados de la campaña de búsqueda de sitios : II - Muñoz, Francisco F. (1963)
This paper is the continuation of paper I (Bol. Asoc. Arg. Astr. 4, p. 61 (1962)) and gives the results obtained during 1962-63. The main results are embodied in the table given in the upper part of page 45, in which the places examined are listed according the percentage of usable nights. In consequence only the three best places (Leóncito, La Pampa and Taninga) are recommended for re-examination.